THE FAILURE OF UNITED NATIONS SYSTEM UNDER INTERNATIONAL LAW: ITS CONTRIBUTION TO CALAMITY AND RUIN OF THE ROHINGYA CASE - Renata Christha Auli (International Law Department, Faculty of Law Universitas Padjadjaran, 2020)
Abstract The tensions between Muslim and Buddhist communities in Rakhine, Myanmar have escalated and became the international spotlight. Massacre in the Rohingya is a serious violation of human rights. In accordance with the functions of the United Nation, this international organization is expected to prevent and eliminate crimes against humanity that occur in the Rohingya. One of the main organs in charge of maintaining international peace and security is the UN Security Council. However, the fact that the United Nations failed to carry out its duties was because Russia has veto power and has blocked the statement which was expressed by UN Security council concerning this situation to punish Myanmar in resolving the Rohingya case, solely due to the political relationship between Russia and Myanmar. The failure of the United Nations is the world's debt to the Rohingya tribe, accordingly to redeem the debt it is needed reform of the UN Security Council. Keywords: Humanitarian Crimes, Rohingya, Security Council, United Nations, Veto Abstrak Perseteruan yang terjadi antara umat Muslim dan Buddha di Rakhine, Myanmar, kembali terjadi dan menjadi sorotan dunia internasional. Pembantaian di Rohingya merupakan pelanggaran berat terhadap hak asasi manusia. Perserikatan Bangsa- Bangsa (PBB) merupakan organisasi internasional yang diharapkan dapat mencegah dan menghapus kejahatan terhadap kemanusiaan yang terjadi di Rohingya, sesuai dengan fungsi dari Perserikatan Bangsa-Bangsa. Salah satu organ utama yang bertugas untuk menjaga perdamaian dan keamanan internasional adalah Dewan Keamanan PBB. Namun fakta yang terjadi PBB gagal dalam menjalankan tugasnya karena Rusia terus melakukan veto terhadap Resolusi Dewan Keamanan PBB untuk menghukum Myanmar dalam penyelesaian kasus Rohingya, karena semata- mata hubungan politik antara Rusia dengan Myanmar. Kegagalan PBB merupakan utang dunia terhadap suku Rohingya, sehingga untuk dapat menebus utang tersebut diperlukan reformasi Dewan Keamanan PBB. Kata Kunci: Dewan Keamanan, Kejahatan Kemanusiaan, Perserikatan Bangsa- Bangsa, Rohingya, Veto